Silenciamento de peroxidase do ascorbato peroxissomal induz mudanças antioxidantes capazes de atenuar estresse oxidativo induzido por excesso de H2O2 na deficiência de catalase - Sousa, Rachel Hellen Vieira de (2014)
The ascorbate peroxidase (APX) and catalase (CAT) are the most important enzymes in removing H2O2 of plant cells. Both are present in peroxisomes. In high photorespiration, the amount of H2O2 in peroxisomes is increased, due to greater activity of glycolate oxidase (GO), enzyme producer of H2O2. Catalase has greater involvement in the removal of H2O2 presenting a high Km and the ability to scavenge higher concentrations of H2O2 than APX. The importance of the peroxisomal isoform of APX in antioxidant metabolism of plant cells is still unknown. There are few papers in literature reporting the role of pAPX. Thus, we performed this work with the objective of evaluating the effect of catalase inhibition in rice plants (APX4) silenced in APX’s peroxisomal isoform. Initially, it was performed a characterization work of three lines of APX4 (Lg, Lh and Lj), aiming to select one line for future studies. It was observed lower GO activity and a slight increase in net photosynthesis in the three mutant lines. Based on biochemical, physiological and photosynthetic parameters, APX4-Lg line was chosen. The APX4 silencing resulted in suppression of expression of the other peroxisomal isoform, APX3. Subsequently, experiments were conducted with catalase inhibition by aminotriazole (AT) in plants NT and APX4. Mutant plants had less electrolyte leakage than NT plants when catalase was inhibited. The synthesis of GSH in the absence of CAT was higher in NT plants. After CAT inhibition, GPX activity increase was higher in APX4 than in NT plants. In order to induce a greater effect of the CAT absence, an experiment was performed combining CAT inhibition with light (1000 μmol photons m -2 s -1), in leaf segments. Similar to the results found in plants, APX4 suffered less than NT plants, with catalase inhibition. APX4 plants also showed higher Fv/Fm, lower electrolyte leakage and lower accumulation of H2O2, in AT+light treatment. Experiments with inhibition of GO were also conducted in order to reduce photorespiration. These results show that plants silenced in APX4 exhibited greater tolerance to inhibition of catalase by a new redox homeostasis able to cope with the catalase inhibition. Further studies are needed to elucidate the mechanisms that APX4 plants have developed to provide better acclimation to catalase inhibition.